1975
DOI: 10.1136/jcp.28.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-negative staphylococci and micrococci in urinary tract infections.

Abstract: SYNPOSIS One hundred catalase-positive, coagulase-negative, Gram-positive cocci isolated in significant numbers from the urine of patients with urinary tract infections, provisionally subdivided by their sensitivity to novobiocin, were classified according to a slightly modified version of BairdParker's schemes (1965 and 1972). It appeared that strains of Micrococcus were nearly all of subgroup 3, and that these were important pathogens of young women presenting with urinary infections in general practice. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…It has been suggested that sensitivity to novobiocin in vitro might be used as a single laboratory test for discriminating between M3 and other biotypes of the Micrococcaceae (Mitchell, 1968;Meers et al, 1975). We found that all strains of micrococci isolated except two of the four strains of M2 and the 11 strains of M7 were resistant to novobiocin, and thaL all strains of staphylococci, with the exception of one strain of Staph.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…It has been suggested that sensitivity to novobiocin in vitro might be used as a single laboratory test for discriminating between M3 and other biotypes of the Micrococcaceae (Mitchell, 1968;Meers et al, 1975). We found that all strains of micrococci isolated except two of the four strains of M2 and the 11 strains of M7 were resistant to novobiocin, and thaL all strains of staphylococci, with the exception of one strain of Staph.…”
Section: Methodsmentioning
confidence: 58%
“…Since Mitchell (1968) reported that staphylococcal infections attributable to abnormalities or instrumentation of the urinary tract were caused predominantly by staphylococcus subgroups II, V, and VI, as defined by Baird-Parker (1963), and infections occurring in otherwise healthy young women by micrococcus subgroup 3 supporting evidence has been accumulating slowly (Mabeck, 1969;Kerr, 1973;Maskell, 1974;Meers, 1974;Meers et al, 1975;Sellin et al, 1975). Mitchell (1968) suggested that micrococcus 3 could be provisionally identified by its resistance to novobiocin in vitro.…”
mentioning
confidence: 99%
“…IA The plasmid profiles of these Imis derivatives appeared to be identical to those of the parent strains, and some of the derivatives may have resulted from the mutagenic action of ethidium bromide and acridine orange. The coagulase-negative staphylococci have considerable clinical significance in their own right (16,22,26,43). Their importance may also extend to acting as a conduit for genes between VOL.…”
mentioning
confidence: 99%
“…However, there are still very few data on the antimicrobial susceptibility of this microorganism (4,5,8,9). We determined the susceptibility of S. saprophyticus to eight antimicrobial agents, and we also determined the activity of five of these agents against isolates of coagulasenegative staphylococci recovered from the urethras of healthy females.…”
mentioning
confidence: 99%